Financial Performance: A Study of CAR and FDR Impact on ROA in Indonesian Islamic Banks - Sulistyorini, Ery; Sarasmitha, Citra; June, Cindy Getah Tresna; Jauhari, Burhanuddin (Business Management Research, 2024)
This research analysis the influence of CAR and FDR on ROA in Sharia Banks during the COVID-19 Outbreak. The phenomenon behind this research is global economic uncertainty due to the pandemic which affects the stability and financial performance of banks, especially Islamic banks. There is a research gap in understanding how financial variables such as CAR and FDR affect ROA in the midst of crisis conditions. This research uses financial report data from Islamic banks in Indonesia during the pandemic period, and the analysis method uses multiple regression. The research results show that CAR and FDR have a significant influence on ROA. These findings indicate that Islamic banks need to maintain and increase CAR and manage FDR well to maintain healthy financial performance. The discussion in this research emphasizes the importance of increasing capital, optimizing financing, and strict regulatory supervision as policy steps that can be implemented. Thus, this research makes an important contribution to the Islamic finance literature and provides practical recommendations for Islamic bank management and regulators to maintain financial stability and health in times of crisis.Keywords: Capital, profitability, sharia banking, COVID-19 pandemic.